Genetic structure and demographic history of Northern Han people in Liaoning Province inferred from genome-wide array data - Zhou, Jingbin; Zhang, Xianpeng; Li, Xin; Sui, Jie; Zhang, Shuang; Zhong, Hua; Zhang, Qiuxi; Zhang, Xiaoming; Huang, He; Wen, Youfeng (Frontiers in Ecology and Evolution, 2022)
In this study, we used typical and advanced population genetic analysis methods [principal component analysis (PCA), ADMIXTURE, FST, f3-statistics, f4-statistics, qpAdm/qpWave, qpGraph, ALDER (Admixture-induced Linkage Disequilibrium for Evolutionary Relationships) and TreeMix] to explore the genetic structure of 80 Han individuals from four different cities in Liaoning Province and reconstruct their demographic history based on the newly generated genome-wide data. We found that Liaoning Han people have genetic similarities with other northern Han people (Shandong, Henan, and Shanxi) and Liaoning Manchu people. Millet farmers in the Yellow River Basin (YRB) and the West Liao River Basin (WLRB) (57–98%) and hunter-gatherers in the Mongolian Plateau (MP) and the Amur River Basin (ARB) (40–43%) are the main ancestral sources of the Liaoning Han people. Our study further supports the “northern origin hypothesis”; YRB-related ancestry accounts for 83–98% of the genetic makeup of the Liaoning Han population. There are clear genetic influences of northern East Asian populations in the Liaoning Han people, ancient Northeast Asian-related ancestry is another dominant ancestral component, and large-scale population admixture has happened between Tungusic Manchu people and Han people. There are genetic differences among the Liaoning Han people, and we found that these differences are associated with different migration routes of Hans during the “Chuang Guandong” period in historical records.